Habitat of Nepenthes spp. in the area of Sampit Botanic Gardens, Central Kalimantan, Indonesia - SYAMSUL HIDAYAT; HENDRA HELMANTO; DODO DODO; DANANG WAHYU PURNOMO; IKAR SUPRIYATNA (Biodiversitas Journal of Biological Diversity, 2018)
Hidayat S, Dodo, Purnomo DW, Helmanto H, Supriyatna I. 2018. Habitat of Nepenthes spp. in the area of Sampit Botanic Gardens, Central Kalimantan, Indonesia. Biodiversitas 19: 1258-1265. Nepenthes spp are protected plant and most of them are at least concern criteria. The research purpose is to explore the habitat information that supports the existence of Nepenthes in the area around Sampit Botanic Gardens, Central Kalimantan. Three different sites have been selected in this research. In each sites, seven sampling plots have been made by purposively sampling, each plot measuring 5x5 m2. In the Gelam Forest (Melaleuca quinquenervia), two Nepenthes species have been found, namely Nepenthes gracilis and Nepenthes mirabilis. In two other sites, in Peat Swamp Forest and Alang-alang Forest (Imperata cylindrica), dominated by N. mirabilis. Combretocarpus rotundatus is a tree in the Peat Swamp Forest that is mostly climbed by Nepenthes. Scleria sumatrensis and Stenochlaena palustris are two species of plants that are always found in the three research sites, but the dominant family is Melastomataceae primarily represented by Melastoma malabathricum. Nepenthes mirabilis can be found in the three research sites with an equal number, but N. gracilis was only abundant in the Gelam forest. By using imageJ software, obtained canopy cover in Gelam forest only 10%. Meanwhile, based on laboratory test, the soil in the Gelam forest is dominated by the dust fraction and is relatively more fertile than the Alang forest. In this case, Nepenthes favored open canopy, but was quite watery and relatively fertile.